2022
DOI: 10.3390/ma15186363
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Porous Asphalt Mixtures Containing Recycled Concrete Aggregate and Fly Ash

Abstract: This study investigates the effects of two waste materials from construction and industry, namely recycled concrete aggregate (RCA) and Type C fly ash, on the overall performance of a special type of pavement surface mixture, porous asphalt mixture. Mixtures of different combinations of RCA (for partial aggregate replacement) and fly ash (for filler replacement) were prepared in the laboratory and tested for a variety of pavement surface performance parameters, including air-void content, permeability, Marshal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 28 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Trematerra and Lombardi [45] x x Mahmud et al [46] x Lou et al [47] x x Shen et al [48] x x Kolodziej et al [49] x [50] x…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trematerra and Lombardi [45] x x Mahmud et al [46] x Lou et al [47] x x Shen et al [48] x x Kolodziej et al [49] x [50] x…”
Section: Resultsmentioning
confidence: 99%
“…Kolodziej et al [49] investigated two different aggregate gradations which are related to different applications across countries, and they showed that when the aggregate gradation content changes, the sound absorption coefficient may increase. In the research of Elmagarhe et al [50], the addition of recycled aggregate to the granite aggregate mixture reduced the sound absorption performance of the porous asphalt mixture. Changing the aggregate type or decreasing the maximum aggregate particle size (from 8 mm to 5 mm) can improve the sound absorption coefficient.…”
Section: The Effect Of the Mixture Content Changementioning
confidence: 96%
“…They compared the results with both PAC and dense-graded asphalt pavements and found that the air temperature above the WRAC pavement was 1 to 2 • C lower than that above a nearby grassed area and 3 to 5 • C lower than that above adjacent rooftops. Elmagarhe et al [19] investigated the effects of the addition of fly ash (FA) on the overall performance of a PAC-10 mixture. They found that the addition of 4% FA reduced the PAC permeability by approximately 12% while also lowering the PAC air void content from approximately 23.5% to 22.95%.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…The use of RCAs has been reported in several works, especially in granular layers [16], but also in asphalt mixtures [17] and concrete, mortars, grouts, and so on {e.g., using recycled concrete fines (mostly non-reactive) as specified in EN 197-6:2023 standard [18]}. In fact, these aggregates have already attracted interest for application in different layers and types of mixtures, mainly in bituminous base and binder courses [19], as well as in dense/semi-dense asphalt mixtures [20], in stone mastic asphalt (SMA) [21], and even in porous asphalt (PA) [22]. In the meantime, its use has been extended to a wide variety of production methods, namely, cold asphalt mixes (CMAs) [23], foamed asphalt mixtures (FAMs) [24], and warm mix asphalt (WMA) [25][26][27], in addition to "traditional" hot mix asphalt (HMA) [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%